Answer:
n = 1
Explanation:
We need to solve this equation for "n".
We first have to recognize the denominator and numerator as a "same" base number.
We know that 216 and 36 can be written as powers of 6. So, we write:
![((6^3)^(n-2))/(((1)/(6^2))^(3n))=216](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qwjdcph4y50k8a3jjzxiosjk3431er848l.png)
Now, we can write the denominator using the rule:
![a^b=(1)/(a^(-b))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/58gjmwapu77t38uz8x74t9j8r8n0dyio5a.png)
So, it becomes:
![((6^3)^(n-2))/(((1)/(6^2))^(3n))=216\\((6^3)^(n-2))/((6^(-2))^(3n))=216](https://img.qammunity.org/2021/formulas/mathematics/middle-school/89cmx4p9qp7rt43potsvfc8aq3yclykiu7.png)
Now, we can use the rule:
![(a^z)^b=a^(zb)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b26w1grne9p476mlh180eopvvl33jkzdw5.png)
So, we have:
![((6^3)^(n-2))/((6^(-2))^(3n))=216\\=(6^(3n-6))/(6^(-6n))=216](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yqsx0jiok0l21e5aftqzryhsxiymj1xvtw.png)
When we have same base, we can write it together using the identity:
![(a^x)/(a^y)=a^(x-y)](https://img.qammunity.org/2021/formulas/mathematics/college/7o9lhbwujzn7m2uaffm5zin6m5m6fw7l71.png)
Thus,
![6^((3n-6)-(-6n))=216](https://img.qammunity.org/2021/formulas/mathematics/middle-school/g9kj7hlpjvvn6u3bgf4tyu8rpvjx6hvvl5.png)
Writing RHS as 6^3 and solving, we have:
![6^(3n-6+6n)=6^3\\6^(9n-6)=6^3\\9n-6=3\\9n=9\\n=1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3vsd3inx2et90ym6sgwkrejm9bj6rbaj2v.png)
Thus,
n = 1